Proceedings of the International Conference on Environmental Awareness for Sustainable Development in Conjunction With Internat 2019
DOI: 10.4108/eai.1-4-2019.2287183
|View full text |Cite
|
Sign up to set email alerts
|

Fermentation Kinetics of Isolate Lactic Acid Bacteria Probiotic BR 12 and BR 17 were Isolated from Broiler Chicken Meat

Abstract: The purpose of this study was to determine the Lineweaver-Burk equation, maximum speed (μmax) and maximum specific / per hour growth rate Ks (constant saturation) of probiotic lactic acid isolates BR 12 and BR 17 with limited sucrose. The material in this study was probiotic isolates of Lactic Acid Bacteria (LAB) BR 12 and BR 17 which were isolated from broiler chicken meat, determined media, and sucrose. The method used was growed probiotic LAB isolates in the media determined with a sukora concentration that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
(10 reference statements)
0
2
0
Order By: Relevance
“…BR 17 isolate was obtained from the isolation of lactic acid bacteria from broiler chicken meat (Mudawaroch et al, 2019) (Mudawaroch et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…BR 17 isolate was obtained from the isolation of lactic acid bacteria from broiler chicken meat (Mudawaroch et al, 2019) (Mudawaroch et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…BR 17 isolate is more efficient in using sucrose when compared to BR 12. BR 17 isolate requires 0.246 g of sucrose in every 100 ml of medium to produce an optimal bacterial growth rate, while BR 12 is 0.34 g/100ml (Mudawaroch et al, 2019) Lactobacillus fermentum can be used as an starter in meat fermentation (Ruiz-Moyano et al, 2011) Traditionally, bacteria were commonly identified through morphological characteristics, metabolites and other phenotypes, and this method was considered inefficient and no longer accurate because it relied on phenotypic expression. There are many differences in results between morphological identification and molecular identification (Ahmadi et al, 2015).…”
Section: Introductionmentioning
confidence: 99%